Peri‐operative nutrition. (January 2016) - Ali Abdelhamid, Y.; Chapman, M. J.; Deane, A. M.
Summary: Patients are frequently malnourished or are at risk of malnutrition before surgery. Peri‐operative nutritional support can improve their outcomes. This review focuses on new developments in peri‐operative nutrition, including: patient preparation and pre‐operative fasting; the role of nutritional supplementation; the optimal route and timing of nutrient delivery; and the nutritional management of specific groups including critically ill, obese and elderly patients.